The sound component in the San Pedro de Casta champeria, Huarochiri - Robles Mendoza, Román (2024)
San Pedro de Casta is a peasant community in the province of Huarochirí, Sierra de Lima. In October they celebrate the big champería festival, as a historical continuity of what their ancestors invented. It is a work party, in which all irrigating community members participate, to maintain the irrigation infrastructure, between traditional rituals, music of chirisuyas, tinyas and choral singing of walinas. By ancient tradition, the champería is directed by the ministers, headed by the Principal, who presides over the rituals and supervises the cleaning of canals and reservoirs. The people participate, organized in four stops: Carhuayuma, Cumao Paccha, Yana Paccha and Hualhualcocha.